Dynamics and Control of the Gyroscopic Head used for the Laser Illumination of a Ground Target from the Quadcopter Deck - Koruba, Zbigniew; Krzysztofik, Izabela (Communications - Scientific Letters of the University of Zilina, 2021)
In the paper authors investigate dynamics of a controlled quadcopter in terms of the possibility of its use for detection, observation, tracking and laser illuminating of both stationary and moving ground targets in the conditions of impact of random and kinematic excitations. The drone is equipped with a scanning and tracking Gyroscopic Head (GH) coupled with a laser target indicator. The drone is affected by random disturbances in the form of wind gusts or explosions of missiles. Kinematic excitations, such as drone maneuvers and vibrations from engines, act on the GH. This paper focuses mainly on control and stabilization of the gyroscopic head placed on the drone during the search, tracking and simultaneous laser illuminating of the target.
Keywords: control and dynamics of quadcopter; scanning and tracking by gyroscopic head; modeling and guidance